Iron industry and Banjar War on the upper of the Barito Watershed, North Barito, Central Kalimantan: Industri besi dan Perang Banjar di hulu DAS Barito, Barito Utara, Kalimantan Tengah - Hartatik Hartatik; Nugroho Nur Susanto; Gaury V. Daneswara; Dian Triasri (BRIN, 2021)
Archaeological research on iron industry in the upper Barito river basin in 2017-2019, show 19 iron ore smelting sites called buren in the local language. Based on radiocarbon dating, the buren was used from 16th to 19th CE. This paper aims to explain correlation between the peak of iron industry in 19th CE and the Banjar War in the upper Barito river, based on a comparison of chronology, type of weapons, and location of buren. Through the historical-archeology approach, the authors suggest that the types of weapons used in the Banjar War have similarities with the inherited weapons of upper Barito people. Several known buren locations also recorded in historical data of the Banjar War. The location of buren shifted from the banks of main river to the banks of tributary river.